X-Ray Lasers 2006 Proceedings of the 10th International Conference, August 20-25, 2006, Berlin, Germany - Nickles, P.V.; Janulewicz, K.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
The search for table-top and repetitive pump schemes during the last decade has been the driving force behind the spectacular advances demonstrated during the 10th International Conference on X-Ray Lasers, organized in 2006 in Berlin. Since 1986, international experts have gathered every two years at this established conference to discuss the progress in theory, experiment and application of plasma-based soft X-ray lasers. Traditionally, the conference sessions devoted to complementary and alternative sources of short wavelength radiation, such as high harmonics, XFEL or incoherent X-rays are organized so as to emphasize the role of X-ray laser research in relation to the other short wavelength sources. Grazing incidence pumping (GRIP) and seeding with high harmonics were the dominant topics of the conference. High repetition rate and portable X-ray lasers were reported to have been applied in metrology and photochemistry for the first time. The proceedings of this series of conferences constitute a comprehensive source of reference of the acknowledged state-of the-art in this specific area of laser and plasma physics. Audience: Researchers and libraries.
Overview of Tabletop X-Ray Laser Development at the Lawrence Livermore National Laboratory -- Advances in High Repetition Rate Soft X-Ray Laser: Lasing Down to 10.9 nm and High Brightness Operation of a Seeded Soft X-Ray Amplifier Using a Solid Target -- Feasibility of 3.4 nm Laser Pumped by Ultraintense RBS Laser -- Collisionally Pumped X-Ray Lasers for Shorter Wavelengths -- Temporal Characterization of Attosecond Harmonic Pulses -- Development of Multilayer Optics for EUV, Soft X-Ray and X-Ray Regions in IPOE -- One Year of User Operation of FLASH, the Free-Electron Laser in Hamburg -- Capillary Discharge Soft X-Ray Laser at University of L’Aquila: Laboratory Survey.
Keywords: Lasers; Photonics; Atoms; Physics; Plasma (Ionized gases).; Physical measurements; Measurement .; Optics, Lasers, Photonics, Optical Devices; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Plasma Physics; Measurement Science and Instrumentation